Evaluation of the State of Aandy Soils on a Sinkhole Area with the use of Noninvasive (MASW) and Invasive (SDMT) Tests - SZAJNA, Waldemar Stanisław (Engineering Transactions, 2015)
The subject of the study is to assess the state of soil in the area of a former shallow underground mining site which presents a potential hazard of sinkholes. Two kinds of tests were performed i.e. noninvasive seismic tests MASW and invasive seismic dilatometer tests SDMT. The test procedures and the used equipment are described in the paper. The MASW tests allowed the detection of shallow and deep seismic anomalies – places with reduced mechanical parameters. Shallow anomalies were subjected to SDMT tests. Stiffness parameters were adopted as a measure of the state of soil. The applied consistent methodology allowed for the assessment of soil stiffness for intermediate and very small strains. It has been shown that the shallow anomalies were not caused by sinkhole processes. The values of stiffness for intermediate and very small strains in the zone above shallow anomalies occurred to be inconsistent, suggesting the influence of cementation or desiccation processes.